Encyclopedia of Polymer Science and Technology 2008
DOI: 10.1002/0471440264.pst562
|View full text |Cite
|
Sign up to set email alerts
|

Polyampholytes

Abstract: This article highlights the synthetic polyampholytes that are able to mimic the behavior of natural polyampholytes, proteins, and illustrates some examples that merge the interface between artificial and natural materials. The electrochemical behavior, solubility, viscosity, mobility, hydrodynamic properties, phase, and conformational transitions of polyampholytes are considered. Adsorption of polyampholytes onto solid, liquid, and gas interfaces is discussed from polarization‐induced attraction forces point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 315 publications
1
18
0
Order By: Relevance
“…[40] Comprehensive reviews on this special class of polymers can be found elsewhere. [40][41][42][43] The use of polyampholyte flocculants is desired when one needs to simultaneously remove more than one contaminant with opposite charges from an effluent. For example, Zhu et al used the amphoteric flocculant poly(ethylene methyl propenoyl-tri-methyl ammonium chloride-co-acrylic acid) to simultaneously flocculate positively charged chromium particles and negatively charged organic particles from a tannery wastewater.…”
Section: Synthetic Flocculantsmentioning
confidence: 99%
“…[40] Comprehensive reviews on this special class of polymers can be found elsewhere. [40][41][42][43] The use of polyampholyte flocculants is desired when one needs to simultaneously remove more than one contaminant with opposite charges from an effluent. For example, Zhu et al used the amphoteric flocculant poly(ethylene methyl propenoyl-tri-methyl ammonium chloride-co-acrylic acid) to simultaneously flocculate positively charged chromium particles and negatively charged organic particles from a tannery wastewater.…”
Section: Synthetic Flocculantsmentioning
confidence: 99%
“…This phenomenon can probably be explained by different hydration degrees of ionic groups leading to 'apparent' decreasing of pore size of cryogels (Table 3). One of the specific features of linear and crosslinked polyampholytes is the existence of so-called isoelectric points (IEPs) where intra-and intermolecular attractions of opposite fixed charges lead to pseudoneutral behavior and compact structure of amphoteric macromolecules [6,7]. Figure 5 shows the swelling and deswelling of amphoteric cryogels as a function of pH.…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic amphoteric gels belong to 'smart' materials due to their response to temperature, pH, ionic strength, water-organic solvent composition, electric field, etc. [6,7]. In the last years the most attention was paid to amphoteric nanogels [8][9][10][11][12][13][14][15] and microgels [16][17][18][19][20] is no any available information on macroporous amphoteric gels of synthetic origin.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, desorption took place in saline medium, evidencing the electrostatic nature of the binding. Nevertheless, the release of protein from polyampholyte—protein associates can take place at the IEP of polyampholytes due to realization of the “isoelectric effect,” that is if the cooperativity of the intrachain interaction of acidic and basic groups within a single macromolecule predominates over those for the interchain interaction …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the release of protein from polyampholyte-protein associates can take place at the IEP of polyampholytes due to realization of the ''isoelectric effect,'' that is if the cooperativity of the intrachain interaction of acidic and basic groups within a single macromolecule predominates over those for the interchain interaction. [20] In this work, we present the results of varying the synthetic strategy on the solubility of the product and on the monomer distribution in the network, keeping the feed ratio, and concentration of the reactive monomers. The innovation consisted in mixing IM and EGDE in a first step making them react at 60 8C, then adding MAA in a second step and incubating at 60 8C for more than 12 h before the radical polymerization induced by benzoyl peroxide.…”
Section: Introductionmentioning
confidence: 99%